2020
DOI: 10.3390/nu12123882
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Consumption and Incident Prefrailty and Frailty in Community-Dwelling Older People: The English Longitudinal Study of Ageing

Abstract: Background: There is limited evidence in the literature regarding associations between fruit and vegetable consumption and risk of frailty. Objective: To examine associations between fruit and vegetable consumption and risk of incident frailty and incident prefrailty/frailty. Design: A prospective panel study. Setting and Subjects: 2634 non-frail community-dwelling men and women aged 60 years or older from the English Longitudinal Study of Ageing (ELSA). Methods: Fruit and vegetable consumption/day was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
2
9
1
1
Order By: Relevance
“…Recent studies provide confirmatory evidence, based on cross-sectional data from mainland China [ 54 ], and longitudinal data from the US [ 55 ] and UK [ 56 ]. For example, in the English Longitudinal Study of Ageing (ELSA), after adjustment for age, sex, smoking, alcohol use, wealth, education, living alone, cognition, depressed mood, diabetes, and hyperlipidaemia, older adults without frailty at baseline who had a daily consumption of 5–10 portions of fruit and vegetables, had a lower risk of incident pre-frailty or frailty when followed-up over four years, although there were no differences among older adults who had very high fruit and vegetable consumption (>10 portions/d) [ 56 ].…”
Section: Foodsmentioning
confidence: 88%
“…Recent studies provide confirmatory evidence, based on cross-sectional data from mainland China [ 54 ], and longitudinal data from the US [ 55 ] and UK [ 56 ]. For example, in the English Longitudinal Study of Ageing (ELSA), after adjustment for age, sex, smoking, alcohol use, wealth, education, living alone, cognition, depressed mood, diabetes, and hyperlipidaemia, older adults without frailty at baseline who had a daily consumption of 5–10 portions of fruit and vegetables, had a lower risk of incident pre-frailty or frailty when followed-up over four years, although there were no differences among older adults who had very high fruit and vegetable consumption (>10 portions/d) [ 56 ].…”
Section: Foodsmentioning
confidence: 88%
“…Plant-based diets are found to be protective against frailty risk [26]. Besides, high consumption of fruits and vegetables, the main sources of antioxidants [27], has been associated with lower risk of frailty [28,29]. In addition, some previous epidemiological studies reported a protective association of a Mediterraneantype diet rather than one food group alone with risk of frailty [30], indicating the potential interactive or additive action between "healthy foods" that may prevent the pathogenesis of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Регулярное употребление овощей и фруктов (оптимально 5 порций, но не менее 2 порций в день) снижает риск развития СА [33,34]. Этот эффект может быть обусловлен витаминами и фитонутриентами, а также пищевыми волокнами, необходимыми для поддержания нормальной кишечной микробиоты.…”
Section: фрукты и овощиunclassified